A case-control study of motor neurone disease: its relation to heritability, and occupational exposures, particularly to solvents. Issue 11 (November 1992) - Gunnarsson, L G; Bodin, L; Söderfeldt, B; Axelson, O
Abstract : Motor neurone disease (MND) was studied in relation to various determinants in a case-control study covering nine counties in southern Sweden. A questionnaire about occupational exposures, medical history, lifestyle factors etc was given to all cases in the age range 45-79 and to a random sample of 500 population controls in the same age range. The questionnaires were answered by 92 cases and 372 controls, a response rate of 85% and 75% respectively. Among men high Mantel-Haenszel odds ratios (MHORs) were obtained for electricity work (MHOR = 6.7, 95% confidence interval (95% CI) 1.0-32.1), welding (MHOR = 3.7, 95% CI 1.1-13.0), and impregnating agents (MHOR = 3.5, 95% CI 0.9-13.1). Heritability with regard to a neurodegenerative disease or thyroid disease seemed to predispose to a risk of developing MND (OR = 2.1, 95% CI 1.0-4.3). The highest OR was found for the combination of such heritability, exposure to solvents, and male sex (OR = 15.6, 95% CI 2.8-87.0), a combination that occurred for seven cases and three controls. Hereditary factors and external exposures had a different distribution among cases with the spinal type of MND than among cases with involvement of the pyramidal tract or bulbar paresis also.